Atmospheric Propagation, Adaptive Systems, and Laser Radar Technology for Remote Sensing 2001
DOI: 10.1117/12.413815
|View full text |Cite
|
Sign up to set email alerts
|

Laser beam propagation through a jet aircraft engine's exhaust

Abstract: One-, half-and ten-micron wavelength radiation was used to study laser beam propagation through turbojet aircraft engine exhaust. A feature of the method was that "instantaneous" distributions of the beam intensity were recorded during the experiment. Analysis of experimental data has shown that turbulent stream has a dramatic impact on spatial characteristics of a laser beam. For example, the averaged angle divergence for 30-mm one-micron beam becomes about ten times higher than its diffraction divergence. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Sometimes, the inverse problem is also studied, that is, the possibility to obtain local or global stochastic properties of the laser beam random propagation using turbulence flow information. About these techniques, we can cite contributions by Wilson [1], Sirazetdinov et al [2], Joia et al [3], Gagnaire and Tailland [4], Benzirar et al [5]. In [1], an experimental method for obtaining statistical properties of turbulent fluctuations in a circular jet is described.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes, the inverse problem is also studied, that is, the possibility to obtain local or global stochastic properties of the laser beam random propagation using turbulence flow information. About these techniques, we can cite contributions by Wilson [1], Sirazetdinov et al [2], Joia et al [3], Gagnaire and Tailland [4], Benzirar et al [5]. In [1], an experimental method for obtaining statistical properties of turbulent fluctuations in a circular jet is described.…”
Section: Introductionmentioning
confidence: 99%
“…In [1], an experimental method for obtaining statistical properties of turbulent fluctuations in a circular jet is described. In [2], it is experimentally proved that the laser angular divergence increases with decreasing cross-angle. Results of different experiments showed that the average angle of the narrow one-micron beam disturbed by a jet aircraft engine is less than that of the ten-micron beam which is characterized by a large diffraction divergence, and that of the half-micron beam stronger subjected to disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…(2), with Cn2 and L0 values selected so as to make analytical calculations fit in with the experimentally obtained distribution for A = 1 .06 pin. Here we were guided by the flict that this particular type of structural function was successfully used for analytical simulation of results obtained earlier in similar experiments for wavelengths of % I .06 tm and A 10.6 Jun [4,5]. The figure presents averaged distributions of radiation intensity in the far.field zone across the beam's diagonal section, since at this stage we disregard distribution asymmetry.…”
Section: Comparison Of Experimental Data With Analytical Relatunshimentioning
confidence: 95%
“…1 . The laser (1) together with the telescopic system (2) expanding the beam, the turning mirror M1 and the receiving system (Oi, 02 lens), W1, W2wedges and CCD-cameras (4,5) were all mounted on a vibration.proofplafform. At the output of the telescopic system a cartridge with removable aperture diaphragms D determining the beam's diameter at the entry into the jet was placed.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…It continues to be of a great interest because of their various technological applications, notably in the domains of engineering [12,13], medical diagnostic [14][15][16][17], electromagnetic interactions with biologic systems [18,19], remote sensing [20][21][22], radars [23][24][25], satellite communications [26], and defence laser weapons [27,28].…”
Section: Introductionmentioning
confidence: 99%